Determinants of firm performance in automotive industry: Empirical insights from Malaysia - Hanaysha, Jalal Rajeh; Saleh, Isam; Suhaidah, Hussain; Lee, Khai Loon; Abu Bakar, Zahari (IGI Global, 2021)
This paper is centered towards examining whether innovation, social media marketing, and corporate social responsibility have any associations with firm performance in automotive sector. By reviewing the prior literature, it can be concluded that there are limited studies which focused on investigating the direct impacts of the above factors collectively on firm performance, particularly in automotive industry. Moreover, the performance of automotive industry in Malaysia has recently experienced slow growth. Therefore, a quantitative research method was employed for data collection and fulfilling the research objectives. In particular, the data were collected via survey instrument from many employees of automotive companies at the state of Pahang in Malaysia. The data was then anlayzed by SPSS Version 19 to verify and test the hypotheses. Overall, the outcomes revealed that innovation has a significant positive impact on firm performance. But the influence of social media marketing on firm performance was found insignificant. Finally, the outcomes showed that the practice of corporate social responsibility has a positive impact on firm performance.